PENGARUH KOMPETENSI PEDAGOGIK TERHADAP PRESTASI KERJA GURU TAMAN KANAK-KANAK KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Rida Yanti; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract : The research aimed to know the effect between pedagogic competence teachers to job performance of kindergarten district Tanah Putih, Rokan Hilir. This research used quantitative research. In this research, the population that used is teachers graduates of D2 the population is number of 35 people. The sample by used of saturated sample. It means that all of the population be samples. The technic of data collection by used a test and questionnaires in the form of a likert scale. The technic of data analysis by used the correlation and analyze that used simple regression analysis with statistic method SPSS for windows version 18. The simple regression analysis to knowing valid or invalid of the effect between pedagogic competence teachers to job performance in kindergarten district of Tanah Putih, Rokan Hilir. It can be seen from r count of 0,226 and 0,344 r table value, because the r count is smaller than the r table or 0,226<0,344. Therefore Ho accepted and Ha rejected. The pedagogic competence give the effect to teachers job performance by of 5%, it showed from R square by of 0,051 and the rest by of 95% it’s because of other variable. So we can conclude there is no effect between pedagogic competence to teachers job performance of kindergarten district of Tanah Putih, Rokan Hilir.Keywords: Pedagogic competence, job performance